MENGEMBANGKAN WARGA BELAJAR YANG UNGGUL DAN BERIMAN: PELATIHAN PENERAPAN SELF-EFFICACY BAGI WARGA BELAJAR PKBM HARAPAN BUNDA KEC. KUALA, KAB. LANGKAT - Donny Adiatmana; Ade Evi Fatimah; Yusrah (Jurnal Pengabdian Kepada Masyarakat, 2022)
In addition to formal education, informal education has an important role in realizing competent Indonesian human resources. The form of strengthening informal education is to maximize the role of the Community Learning Activity Center. The Community Learning Activity Center has the principle of long-life education where every community has the right to get a proper education so that citizens are created superior and faithful. To realize excellence and faith, we need an appropriate concept and technique to motivate learning citizens. Self-efficacy is a concept that encourages learning citizens to grow motivation in themselves so that they are confident in solving problems and being able to achieve their dreams. The location for the implementation of community service is at PKBM Harapan Bunda located in Hamlet 1 Belilir, Balai. Kasih Village. The method of implementing the activities consists of case studies, brainstorming and focus group discussions. There are 15 learning residents who take part in this community service activity. The results of the activity showed that the residents were enthusiastic and active while participating in this community service activity. The team also conveyed motivations for learning citizens to stay enthusiastic about learning